2018
DOI: 10.1038/nature25758
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the D2 dopamine receptor bound to the atypical antipsychotic drug risperidone

Abstract: Summary Dopamine is a neurotransmitter that has been implicated in processes as diverse as reward, addiction, control of coordinated movement, metabolism and hormonal secretion. Correspondingly, dysregulation of the dopaminergic system has been implicated in diseases ranging from schizophrenia, Parkinson’s disease, depression, attention deficit hyperactivity disorder, nausea and vomiting, among others. Dopamine’s actions are mediated by a family of five G-protein coupled receptors (GPCRs) (viz. D1, D2, D3, D4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
441
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(471 citation statements)
references
References 48 publications
25
441
2
3
Order By: Relevance
“…Thus, we infer that the distinct conformation of Trp100 EL1.50 in the D2R structure is a combined effect of the helical EL2 conformation and the favored interaction that Trp100 EL1.50 can form with bound risperidone in the crystal structure, the latter of which however, has a minimal influence on the binding affinity of risperidone 10 , consistent with the unstable interaction between risperidone and Trp100 EL1.50 in our simulations ( Fig. 4, Supplementary Movie 2).…”
Section: Both El2 Conformation and Ligand Scaffold Affect The El1 Consupporting
confidence: 82%
See 3 more Smart Citations
“…Thus, we infer that the distinct conformation of Trp100 EL1.50 in the D2R structure is a combined effect of the helical EL2 conformation and the favored interaction that Trp100 EL1.50 can form with bound risperidone in the crystal structure, the latter of which however, has a minimal influence on the binding affinity of risperidone 10 , consistent with the unstable interaction between risperidone and Trp100 EL1.50 in our simulations ( Fig. 4, Supplementary Movie 2).…”
Section: Both El2 Conformation and Ligand Scaffold Affect The El1 Consupporting
confidence: 82%
“…This is consistent with our simulation results that show the I122 3.40 A mutation has minimal impact on risperidone binding. Both Ile122 3.40 and Phe382 6.44 of the Ile122 3.40 sub-pocket are part of the conserved Pro 5.50 -Ile 3.40 -Phe 6.44 motif that undergoes rearrangement upon receptor activation 17 , and we have found that the I122A mutation renders the receptor non-functional 10,18 . Thus, the I122A mutation may promote an inactive conformation of D2R that favors eticlopride binding but has no effect on the binding of risperidone or spiperone.…”
Section: Mutagenesis Of Ile122 340 and The Sensitivity To Na +mentioning
confidence: 67%
See 2 more Smart Citations
“…Dopamine (DA), a typical neurotransmitter, plays a critical role in the central nervous systems to control reward-related behaviors, movement initiation, release of hormones, etc. [1][2][3] An abnormal level of DA can lead to severe diseases, such as Parkinson's, [4] schizophrenia, [5] and depression. [6] The reliable and accurate detection of DA, however, is not easy.…”
Section: Highly Sensitive and Selective Electrochemical Detection Ofmentioning
confidence: 99%